2014
DOI: 10.2174/1874325001408010194
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Bite Injuries to the Hand and Their Management

Abstract: Bite wounds are a common form of hand injury with the potential to lead to severe local and systemic sequelae and permanent functional impairment. Mammalian bite wounds may be caused by a variety of animal class and species; injuries resulting from dogs, cats and humans are the most widely discussed and reported in the literature. Bite wounds may be contaminated with aggressive pathogens and the anatomical vulnerability of structures within the hand means that without early recognition and treatment with irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 48 publications
0
16
0
12
Order By: Relevance
“…The purpose of surveillance of rabies in Iran is the prevention of animal bite cases that cause fatal disease of rabies since millions of dollars are allocated annually to buy the rabies virus vaccine [7]. Gonabad city has industry livestock and a huge number of domesticated dogs, thus has the most reported animal bites from these dogs as compared to other animals.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of surveillance of rabies in Iran is the prevention of animal bite cases that cause fatal disease of rabies since millions of dollars are allocated annually to buy the rabies virus vaccine [7]. Gonabad city has industry livestock and a huge number of domesticated dogs, thus has the most reported animal bites from these dogs as compared to other animals.…”
Section: Discussionmentioning
confidence: 99%
“…Jha S et al 51 (2014) found that bite wounds are a common form of hand injury with the potential to lead to severe local and systemic sequelae and permanent functional impairment. Bite wounds can be injuries resulting from the bites of various animals like dogs, cats and even humans and these are the most widely discussed and reported in the literature.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Jha S et al 51 (2014) found that Bite wounds may be contaminated with aggressive pathogens and the anatomical vulnerability of structures within the hand means that without early recognition and treatment with irrigation and antibiotics, alongside a low index of suspicion for deep structural involvement requiring formal surgical exploration and washout, the consequences of such injuries can be disastrous.…”
Section: Fractures and Dislocationmentioning
confidence: 99%
“…No significant delay had occurred in seeking care, with an ambulance having been called 10-15 minutes post incident. Delay in seeking attention and treatment is shown to significantly increase the likelihood of infection and the need for surgical intervention (Maimaris and Quinton, 1988;Jha et al, 2014). Risk factors which would adversely affect the patient's ability to heal normally, such as chronic disease states including diabetes, liver cirrhosis, renal failure, chronic obstructive pulmonary disease, anaemia, and peripheral vascular disease were excluded.…”
Section: The Casementioning
confidence: 99%
“…This comparatively low infection rate increases with bites to the hand (28% to 47%), where the anatomy, which comprises multiple compartments, and scant presence of soft tissue between skin and bone, lends to potential bacterial infiltration and propagation via structures such as tendons, ligaments and bones (Morgan and Palmer, 2007;Kennedy et al, 2015). It is suggested that 62% of wounds overlying metacarpophalangeal or proximal interphalangeal joints demonstrate penetration of the joint space below (Jha et al, 2014). Complications can include cellulitis, abscess, septic arthritis, osteomyelitis, tenosynovitis, and severe sepsis.…”
Section: Bites To the Handmentioning
confidence: 99%